Root Studies: What is New? An Extension to a Previous Review of 2013 - Silberbush, Moshe (Recent Progress in Plant and Soil Research Vol. 1, 2021)
Root studies of recent years include modeling of the soil-root system to quantify the performance of the such complex system. Recent developments in computer sciences and technologies made it more available to the users, either of computer sciences, engineering and life sciences. Still, certain restrictions are there, due to the fact that evolution of million of years of adaptation to live of plants on soil, involve life on thresholds between phases of roots-soil surfaces, that mathematics and computer science still unable to properly deal with. The technological progress seems promising. In this extension to a previous review, I survey the progress in modeling of uptake by roots from soils in recent years. I find certain improvements, but basic problems are still unsolved. These are mainly of uptake along roots, interactions between nutrient in the soil-root interfaces, and of roots and biological and micro-biological interactions with the soil micro-flora.